(untitled) (Research, Society and Development, 2020)
This text aims to investigate the challenges faced by teachers at Franklin Távora High School (Itapiúna-CE) in relation to inclusive education. For that, a qualitative research was carried out, contemplating the case study, analyzing the way inclusive education is understood in high school, from the perspective of the teachers. As a strategy to approach reality, a questionnaire was used with the teachers of that school. The study made it possible to verify that there is a gap in teacher education, when related to inclusive education. The concern with the specific training of Inclusive Education teachers, who are living with the practice of school inclusion, has become the main challenge among many others that directly affect the inclusion of students with disabilities in Secondary Education in the city of Itapiuna-CE . More studies, research and pedagogical support are needed so that inclusive education will gain greater prominence in the local scenario, since the potential of students is not limited to a disability.